Perbandingan Test Case Generation dengan Pendekatan Genetic Algorithm Mutation Analysis dan Sampling - Christopher Dimas Satrio; Mochamad Chandra Saputra; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Software testing has an important role to knowing and maintaining the quality of a software. In software testing process, test case is necessary. However, test case generation require a relatively long time, so automatic test case generation with a certain algorithm are conduct. The purpose of this research are to compare genetic algorithm mutation analysis and genetic algorithm sampling approach. That's two approach wil be implemented and analyzed the result. In terms of the final result, will be revealed the reduction of the number of test case that occurs. Number of iteration, cumulative number of individuals, number of fitness evaluation, and size of the resulting test suites will be variable comparison between that's two approach. The conclusion of this research are the genetic algorithm mutation analysis approach is better than genetic algorithm sampling approach in terms of the reduction number of test case and for all comparison variable that applied.